PENGARUH PENGGUNAAN MEDIA POP UP BOOK TERHADAP KECERDASAN LINGUISTIK ANAK USIA 5-6 TAHUN DI RA NURHAYATI KECAMATAN MEDAN TEMBUNG - Desi Maisura Sidabutar; Khadijah Khadijah; Rohani Sitorus (JURNAL RAUDHAH, 2019)
This research was conducted in RA Nurhayati, Medan Tembung District, on February 25 to March 9, 2019. The type of research carried out was an experimental study with a quantitative approach. This research method uses Quasi Experimental Designs with Non Equevalent Control Group Design. The population of 29 children by sampling using the Total Sampling technique, so that the entire population is used as a sample. This study aims to determine: (1) Children's linguistic intelligence (2) Children's linguistic intelligence using pop up book media (3) Significant influence of pop up book media on children's linguistic intelligence in RA Nurhayati District Medan Tembung T.A. 2018/2019. The results showed that the use of pop-up media influenced linguistic intelligence of children aged 5-6 years. This is illustrated by the results of the study obtained an average pre-test 26.72 and an average post-test of 52.08. So that the linguistic intelligence of children in the experimental class is better than the control class with an average pre-test 25 and an average post-test of 44.83. Based on the results of hypothesis testing obtained tcount> ttable is 3.226> 2.131 with a significant number of α = 0.05. Thus the hypothesis Ho is rejected and Ha is accepted so that it can be stated There is a Significant Effect of the Use of Pop Up Book Media on Linguistic Intelligence of Children Aged 5-6 Years in RA Nurhayati Medan Tembung District T.A. 2018/2019.